Negative feedback loop of ERK/CREB/miR‐212‐3p inhibits HBeAg‐induced macrophage activation. Issue 18 (7th August 2020) - Chen, Wenjun; Bian, Hongjun; Xie, Xiaoyu; Yang, Xia; Bi, Benjun; Li, Chunliu; Zhang, Yuejuan; Zhu, Qiang; Song, Jing; Qin, Chengyong; Qi, Jianni
Abstract: The activation of liver macrophages is closely related to liver injury after HBV infection. Our previous results demonstrated that HBeAg played a key role in inducing macrophage activation. As we all know, miRNAs are involved in the regulation of multiple immune cell functions. Meanwhile, we have shown that miR‐155 positively regulates HBeAg‐induced macrophage activation and accelerates liver injury. Subsequently, based on our previous miRNA sequencing results, we further evaluated the role of miR‐212‐3p called 'neurimmiR' in HBeAg‐induced macrophages in this study. First, miR‐212‐3p expression was significantly elevated in HBeAg‐treated macrophages. Meanwhile, we found up‐regulation of miR‐212‐3p significantly decreased the production of cytokines, whereas knockdown of miR‐212‐3p held the opposite effect by gains and losses of function. Mechanically, although MAPK signal pathway, including ERK, JNK and p38, was activated in HBeAg‐induced macrophages, only ERK promoted the expression of miR‐212‐3p via transcription factor CREB, which was able to bind to the promoter of miR‐212‐3p verified by ChIP assay. Moreover, we further indicated that up‐regulated miR‐212‐3p inhibited HBeAg‐induced inflammatory cytokine production through targeting MAPK1. In conclusion, miR‐212‐3p was augmented in HBeAg‐stimulated macrophages via ERK/CREB signal pathway and the elevated miR‐212‐3p suppressed inflammatory cytokine production induced by HBeAg through targeting MAPK1.